Isolation and characterization of free-living nitrogen fixing bacteria from alkaline soils - Smita, Madhu; Goyal, Dinesh (International Journal of Scientific World, 2016)
Free living nitrogen fixing bacteria were isolated from soil on Jensen agar plates and were characterized phylogenetically by 16S rDNA sequence analysis. All the isolates (VS1, VS2, VS3, VS4) were Gram –ve, rod shaped. Antibiotic test revealed VS2 to be resistant to ampicillin and VS4 was resistant to both ampicillin and kanamycin; otherwise all the isolates were sensitive to chloramphenicol. Nitrogen fixation was studied by the estimation of total nitrogen and available nitrogen fixed by cultures in the medium and compared with the control culture of Azotobacter CBD15 (Azo) procured from IARI. VS2 and VS3 fixed 12.02 ppm/ml and 10.635 ppm/ml as available nitrogen content and 14.44 ppm/ml and 18.73 ppm/ml as total nitrogen content. 16S rDNA studies revealed identification of the isolates- Pseudomonas sp. (VS2) and Paenibacillus sp. (VS3 and VS4). VS3 and VS4 showed 98% similarity with P. borealis. Soils from which these microbes isolated were also characterized to understand the environment of these microbes. The pH and chemical characterization (Organic Carbon, Phosphorus, Sulphur, heavy metal analysis of different metals e.g. Zn, Cu, Cr, Pb, Ni and water holding capacity) of the soils showed them to be slightly alkaline and clayey loamy. Cloning of VS2 was done successfully with plasmid pMMB277 isolated from E. coli 2842.The significance of this study lies in the isolation of those bacteria which are comparable in their nitrogen fixing potential to Azotobacter.